2012
DOI: 10.5601/jelem.2009.14.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Copper, zinc, iron and manganese content in edible parts of some fresh vegetables sold on markets in Poznań

Abstract: Copper, zinc, iron and manganese contents were determined in edible parts of some fresh vegetables sold on markets in Poznañ. The copper and zinc contents in vegetables obtained in the present study were compared to the ones reported from an analogous study carried out in the Department of Horticultural Plant Fertilization in Poznañ fifteen years ago. Samples of vegetables were collected from six points distributed in the area of Poznañ from March to July at monthly intervals. For the study, vegetables were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 1 publication
1
13
1
Order By: Relevance
“…The maximum Zn content in the carrot leaves was observed at a dose of 230 mg kg -1 of Zn in the soil. This possibly indicates that, beginning at this concentration in the soil, a phytotoxic effect occurred with the consequent development of disturbances in the plant (Bosiacki and Tyksiñski, 2009), inhibiting its absorption and allocation to the leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum Zn content in the carrot leaves was observed at a dose of 230 mg kg -1 of Zn in the soil. This possibly indicates that, beginning at this concentration in the soil, a phytotoxic effect occurred with the consequent development of disturbances in the plant (Bosiacki and Tyksiñski, 2009), inhibiting its absorption and allocation to the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…These leafy vegetables presented higher potential for transferring Zn from the soil to their edible parts compared with other horticultural plants (Bosiacki & Tyksiñski, 2009). These results demonstrate the differences among species in relation to the capacity to absorb and concentrate Zn in tissues (Yang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The mean concentration recorded was (51.90 ± 25.40 µg/g-dw). Similar studies [27,32] also reported levels of Zn in onions, carrots, cabbages, and tomatoes above permissible levels of FAO/WHO.…”
Section: Zincmentioning
confidence: 56%
“…Similar studies [16,27,31,32] recorded the concentration of copper below permissible limit in cabbages, carrots and tomatoes. With exception of onions at Kihonda (7.19 µg/g-dw) and carrots at Towelo (6.11 µg/g-dw), vegetables are safe from Cu contamination in both areas.…”
Section: Coppermentioning
confidence: 65%
“…The concentration range of Mn in this work is within the values recently reported in 6 out of 9 spice studies (Table 7). In comparison to other plants, the Mn content was somewhat higher than the range recorded for a large number of vegetable samples [36].…”
Section: Manganesementioning
confidence: 88%